Quality and fatty acid profiles of fish oil from tuna by-products extracted using a dry-rendering method - HEDER DJAMALUDIN; TITIK DWI SULISTIYATI; ANIES CHAMIDAH; PUTRI NURASHIKIN; MIFTAHUR ROIFAH; HARTOYO NOTONEGORO; PAMUNGKAS RIZKI FERDIAN (Society for Indonesian Biodiversity, 2023)
Abstract. Djamaludin H, Sulistiyati TD, Chamidah A, Nurashikin P, Roifah M, Notonegoro H, Ferdian PR. 2023. Quality and fatty acid profiles of fish oil from tuna by-products extracted using a dry-rendering method. Biodiversitas 24: 5757-5763. Tuna is an export commodity with a high-fat content, making it a valuable source of fish oil. However, a substantial portion of tuna, including viscera, eyes, and liver, some parts are underutilized, leading to waste. The study aims to determine the impact of extraction temperature (50°C, 60°C, and 70°C) on the yield, peroxide value, free fatty acids (%), p-anisidine value, and total oxidation value of the extracted oil from tuna (Euthynnus sp.) by-products. This research used the dry-rendering method to extract crude oil from tuna by-products and analyze quality characteristics and fatty acids. The results from the proximate value indicated that the crude lipid content in tuna by-products ranged from 13.03% to 19.01%. Extraction temperature significantly affected the yield, with the highest yield at 70°C correlating with the highest lipid content in innards. The lowest peroxide value is obtained from an extraction temperature of 50°C from all parts of tuna by-products, ranging from 2.01 to 2.09 meq/kg. Free fatty acid (%) levels in this study met the International Fish Oil Standards (IFOS), and different temperature treatments had a significant effect (P<0.05). The lowest value of p-anisidine, 6.11 meq/kg, was obtained from an extraction temperature of 50°C for innards samples, and the p-anisidine value increased with temperature, reflecting secondary oxidation products. The total oxidation lowest value was obtained from extraction at 50°C (14.84 meq/kg) from viscera by IFOS (?20 meq/kg), and it was within acceptable limits. The fatty acid profile of the crude extract of tuna by-product oil resulting from extraction at a temperature of 50°C, where extraction results at 50°C obtained a fatty acid profile of saturated fatty acids>mono-unsaturated fatty acids>polyunsaturated fatty acids, with significant levels of omega-3 fatty acids such as eicosapentaenoic acid and docosahexaenoic acid.